Dual DC current injection‐based stator winding temperature tracking for dual three‐phase permanent magnet synchronous machine using Kalman filter. Issue 11 (23rd May 2019) - Li, Ze; Feng, Guodong; Lai, Chunyan; Tian, Jiangbo; Li, Wenlong; Kar, Narayan C.
Abstract : To prevent motor failures caused by thermal overloading, accurate knowledge of stator winding temperature is of significance. The proposed stator winding temperature tracking is a stator resistance‐based estimation technique for dual three‐phase permanent magnet synchronous machines. In the proposed approach, a dual DC signal‐injection‐based method is developed to determine winding temperature accurately, which is capable of cancelling the voltage‐source inverter non‐linearity effect with no interference with torque output. Meanwhile, the proposed method is not affected by magnetic saturation because of no inductance terms involved. The Kalman filter is employed to improve the performance of winding temperature estimation. Moreover, the proposed approach is independent of operating conditions and can be implemented in a standard motor drive with a minimum computational cost. The experimental results validate the proposed approach on a laboratory dual three‐phase interior permanent magnet synchronous motor under various speeds and load conditions.